2015
DOI: 10.1002/2015jd024238
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for added value of convection‐permitting models for studying changes in extreme precipitation

Abstract: Climate model resolution can affect both the climate change signal and present-day representation of extreme precipitation. The need to parametrize convective processes raises questions about how well the response to warming of convective precipitation extremes is captured in such models. In particular, coastal precipitation extremes can be sensitive to sea surface temperature (SST) increase. Taking a recent coastal precipitation extreme as a showcase example, we explore the added value of convection-permittin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 55 publications
0
40
0
Order By: Relevance
“…Changes in precipitation extremes are primarily influenced by changes in large-scale circulation over the tropics (Maredith et al 2015). Most of the reanalysis datasets reasonably reproduce the climatological circulation features.…”
Section: Climatological Features Over the Asian Domainmentioning
confidence: 87%
“…Changes in precipitation extremes are primarily influenced by changes in large-scale circulation over the tropics (Maredith et al 2015). Most of the reanalysis datasets reasonably reproduce the climatological circulation features.…”
Section: Climatological Features Over the Asian Domainmentioning
confidence: 87%
“…Recent sensitivity studies of Regional Climate Models, for example, have suggested that they cannot adequately reproduce high intensity convective rainstorms and consequently might not be fit-forpurpose in predicting conditions for future flooding induced by such events (e.g. Kendon et al, 2014;Meredith et al, 2015).…”
mentioning
confidence: 99%
“…The method generally performs better in JJA than in DJF and in DJF best in the Mediterranean region, with a mild winter climate, and worst for the continental winter climate in Midand eastern Europe or Scandinavia. Seasonal and regional differences depending on the underlying mechanism have al-ready been reported for resolution dependence of extreme precipitation in GCMs (Volosciuk et al, 2015) and RCMs (Prein et al, 2013;Meredith et al, 2015). Hence, for a good representation of precipitation extremes, the complexity of the model can be chosen at each step of the modeling cascade based on the underlying mechanism in order to use computational resources efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…Our model is thus only applicable where changes are correctly simulated by the GCM/RCM. For instance, changes in the dynamics of local extreme convective events in summer that need even higher resolution up to convection-permitting simulations (e.g., Kendon et al, 2014;Chan et al, 2014;Meredith et al, 2015) will also not be represented after statistical postprocessing is applied. Bias correction and (dynamical and statistical) downscaling of precipitation is only applicable if the large-scale patterns and changes therein are simulated reasonably by the driving GCM (Eden et al, 2012;Hall, 2014).…”
Section: Discussionmentioning
confidence: 99%